1996
DOI: 10.1037/h0080192
|View full text |Cite
|
Sign up to set email alerts
|

Children of adolescent mothers: Attachment representation, maternal depression, and later behavior problems.

Abstract: Underlying the responses of 34 44-month-old children of adolescent mothers to five attachment narratives were two factors--departure and reunion. The departure factor included disorganized and insecure responses to parents' departure as well as disorganized responses to narratives about children's misbehavior and fear. Scores predicted children's externalizing behavior problems 10 months later and discriminated children in the clinical from those in the normal range for externalizing problems. Maternal depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…As might be expected on the basis of Bowlby's theorizing, the representational attachment assessments also predicted pre-schoolers' social behavior with peers (Cho, 1994;Goldwyn, Stanley, Smith, & Green, 2000;Kim, 1992;Oppenheim, 1997;Verschueren, Marcoen, & Schoefs, 1996). In addition, Hubbs-Tait et al (1996) and Oppenheim, Emde, & Warren (1997) reported signi cant associations between maternal ratings of behavior problems and story completions, though, paradoxically, these effects were reversed in the study by Goldwyn et al (2000), for internalizing (not externalizing) problems. A detailed review and evaluation of these reports can be found in Page (in press).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…As might be expected on the basis of Bowlby's theorizing, the representational attachment assessments also predicted pre-schoolers' social behavior with peers (Cho, 1994;Goldwyn, Stanley, Smith, & Green, 2000;Kim, 1992;Oppenheim, 1997;Verschueren, Marcoen, & Schoefs, 1996). In addition, Hubbs-Tait et al (1996) and Oppenheim, Emde, & Warren (1997) reported signi cant associations between maternal ratings of behavior problems and story completions, though, paradoxically, these effects were reversed in the study by Goldwyn et al (2000), for internalizing (not externalizing) problems. A detailed review and evaluation of these reports can be found in Page (in press).…”
mentioning
confidence: 76%
“…Bretherton, Ridgeway & Cassidy, 1990;Cassidy, 1988) or a score for positive coping (e.g. Hubbs-Tait et al 1996), to interpret children's responses. In this study, by contrast, we focused on identifying themes that can provide more detailed information regarding the content of children's attachment experiences.…”
Section: IV O R C E a N D C H Il D R E N 'S E M O T Io N A L S Ec Umentioning
confidence: 99%
“…Using the ASCT with 44-month-old children of adolescent mothers, Hubbs-Tait, Hughes, and Culp (1996) found that children's narrative enactments were associated with subsequent externalizing behaviors but not with internalizing behaviors. In addition, prosocial and affiliative themes coded from middle SES children's story stem enactments have been associated with fewer externalizing behavior problems and lower teacher-rated hostility (Oppenheim, Nir, Warren, & Emde, 1997;Warren, Oppenheim, & Emde, 1996;ZahnWaxler, Friedman, Cole, Mizuta, & Hiruma, 1996).…”
Section: Assessment Of Attachment Relationshipsmentioning
confidence: 98%
“…However, the parent–child relationship can be affected by several psychosocial and socio-demographic risk factors that undermine its quality and in turn play a negative role in short and long term child psychological wellbeing (Sameroff, 1998, 2000; Choe et al, 2013). Classical research on the psychological development of children living in at risk families supports additive models according to which psychological problems are not the result of one specific risk factor but may be instead predicted by the combined presence of different factors (Greenberg et al, 1993; Lyons-Ruth et al, 1993; Hubbs-Tait et al, 1996). Also, established models of parenting (Belsky, 1984) postulate that the quality of the parent–child relationship is the integrated result of three sets of factors: parent characteristics, infant characteristics, and context which can influence parenting in a supportive or stressful way.…”
Section: Introductionmentioning
confidence: 99%